Mitigasi Bencana Tanah Longsor Berbasis Pemberdayaan Masyarakat di Kecamatan Pacet Kabupaten Mojokerto - Johan Paing Heru Waskito; Danang Setiya Raharja; Akhmad Maliki (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2026)
Pacet Subdistrict, Mojokerto Regency, is a hilly and mountainous area with a high level of vulnerability to landslide disasters, particularly during the rainy season with high rainfall intensity. The major landslide that occurred along the Pacet–Cangar route in April 2025, resulting in fatalities and the disruption of interregional transportation access, serves as clear evidence of the urgent need to strengthen disaster mitigation efforts in this area. This scientific article aims to examine and describe community empowerment–based landslide disaster mitigation initiatives implemented through community service activities conducted by a team from Universitas Wijaya Kusuma Surabaya. The methods employed include community education and training, the establishment of disaster preparedness communities, cross-sectoral coordination, and the strengthening of environmental awareness. The results indicate a significant increase in community understanding of landslide mitigation, as demonstrated by comparisons between pre-test and post-test results, as well as the formation of a community-based disaster response group that plays an active role in preparedness efforts. This article emphasizes that effective disaster mitigation depends not only on technical approaches but also on strengthening social capacity and fostering sustainable multi-stakeholder collaboration